Decision of the Panel of Judges About Mafqud legacy (Study of Normative Juridical Analysis at the Medan City Religious Court) - Muhammad Yusuf; hafsah hafsah; Dhiauddin Tanjung (DE LEGA LATA: JURNAL ILMU HUKUM, 2023)
This study aims to determine the method of the panel of judges of the Medan City Religious Court in taking law in mafqud inheritance cases, to find out the results of the decision of the panel of judges of the Medan City Religious Court in the case of mafqud inheritance, and to find out whether the decision of the panel of judges of the Medan City Religious Court in taking law in cases of mafqud inheritance is in accordance with the principles of justice and legal norms. This research method consists of several things: the type of research is empirical-juridical-normative, and the approach (approach) used is the statute approach, namely the decision approach of the Medan City Religious Court. Sources of data consist of observations, interview results, and results of documentation with Medan Religious Court Judges. The results of the research are as follows: The method of the panel of judges at the Medan City Religious Court in taking law in mafqud inheritance cases, which is almost the same as the methodology in other cases submitted to the Medan City Religious Court, is by following the formal legal rules and material law contained in the Code of Procedure Civil Code (KUHPerd.). The results of the decision of the panel of judges at the Medan City Religious Court in the mafqud inheritance case are that in four cases, three requests were granted, namely Determination Number 73/Pdt.P/2011/PA.Mdn., Determination Number 213/Pdt.P/2017/PA.Mdn., and Determination Number 68/Pdt.P/2018/PA.Mdn., while one case cannot be accepted, namely the lawsuit (contentious) in Decision Number 2317/Pdt.G/2017/PA.Mdn. The decision of the panel of judges at the Medan City Religious Court in taking law in the mafqud inheritance case was in accordance with the principles of justice and legal norms; in general, it fulfilled the principles of justice. On the other hand, there were decisions of the assembly that were inconsistent with the principle of equality before the law (equality before the law), as in cases of lawsuits that were not granted by the judge for reasons that were not strong in the author's analysis. The standardization of statements concerning a person's mafqud, including both heirs and heirs. In cases of application (volunteer), it seems that it is very easy to determine who is mafqud, whereas in lawsuits (contentious), the judge is very thorough and very strict in examining someone who is mafqud. Besides that, there is a disregard for the rights of the heirs of the heir's siblings who are mafqud, which is contradictory with the principles of Islamic inheritance law